Hubungan Tingkat Pengetahuan Perawat dengan Stigma Perawat terhadap ODHA (Orang dengan HIV/AIDS) - Monalisa Palalangan, Monalisa Palalangan; Tutik Rahayu; Hernandia Distinarista (STIKes Ibnu Sina Ajibarang, 2025)
The knowledge and acceptance of nurses toward patients with HIV/AIDS (PLHIV) play a crucial role in improving the quality of nursing care. A lack of knowledge and insufficient understanding can lead to poor care quality and health outcomes for PLHIV patients. This study aims to analyze the relationship between nurses' knowledge level and stigma toward PLHIV. This study used a correlational analytic design with a cross-sectional approach, where data were collected from 63 respondents, consisting of nurses working in hospitals, specifically in the PLHIV wards. Data were analyzed using the Chi-Square test to examine the relationship between the variables of nurses' knowledge and stigma toward PLHIV. The results showed that 63.5% of nurses had adequate knowledge about HIV/AIDS, while 14.3% had insufficient knowledge. The majority of nurses working in PLHIV wards demonstrated sufficient understanding, which could potentially influence their acceptance attitude toward patients. Statistical analysis revealed a significant relationship between nurses' knowledge level and stigma toward PLHIV (p < 0.05). This highlights the importance of improving nurses' competence through continuous training and education to reduce stigma and enhance professionalism in providing care to PLHIV patients. This study is expected to serve as a basis for the development of educational and training programs for nurses to improve their understanding of HIV/AIDS and minimize stigma toward PLHIV.